Implementation of 3000-watt inverter as a source of electrical energy in solar power plants - Partaonan Harahap; Noorly Evalina; Faisal Irsan Pasaribu; Rimbawati Rimbawati; Benny Oktrialdi; Rahmatullah Rahmatullah; Munawar Alfansury Siregar (Politeknik Negeri Lhokseumawe, 2023)
In industry, an inverter is a tool/component for adjusting the speed of an electric motor. By using an inverter for electric motor purposes, it becomes a variable speed, whereas the speed can be changed or adjusted as needed. The method used in this study is an experimental research method, namely designing and measuring the system under study. Measurements are made for non-electrical quantities, namely the inverter of the solar module which is generated by the intensity of sunlight hitting the surface of the solar cell. Measurements are also made for electrical parameters such as current, voltage, power factor, and power. Based on the data obtained from all the tests that have been carried out, the system output voltage cannot reach the expected 220 Volts. Because changes in load affect the output voltage of the system were occurred, as the load of 60 W/220V is added, the output voltage drops to 740.5 Volts. As the load is reduced by 60W/220 V, the output voltage increases by 786.9 Volts, within the average inverter efficiency of 77%.